African pastoralism: Genetic imprints of origins and migrations - Hanotte, Olivier H.; Bradley, D.G.; Ochieng, J.W.; Verjee, Y.; Hill, E.W.; Rege, J.E.O. (American Association for the Advancement of Science, 2002)
The genetic history of African cattle pastoralism is controversial and poorly understood. We reveal the genetic signatures of its origins, secondary movements, and differentiation through the study of 15 microsatellite loci in 50 indigenous cattle breeds spanning the present cattle distribution in Africa. The earliest cattle originated within the African continent, but near East and European genetic influences are also identified. The initial expansion of African Bos taurus was likely from a single region of origin. It reached the southern part of the continent by following an eastern route rather than a western one. The B. indicus genetic influence shows a major entry point through the Horn and the East Coast of Africa and two modes of introgression into the continent.